Modern romance - Ansari, Aziz 1983- (Penguin Press, 2015)
The acclaimed comedian teams up with a New York University sociologist to explore the nature of modern relationships, evaluating how technology is shaping contemporary relationships and considering the differences between courtships of the past and present
Includes bibliographical references (pages [257]-266) and index
Searching for your soul mate -- The initial ask -- Online dating -- Choice and options -- International investigations of love -- Old issues, new forms : sexting, cheating, snooping, and breaking up -- Settling down
Keywords: Man-woman relationships; Man-woman relationships / Humor; Dating (Social customs); Dating (Social customs) / Humor; Courtship; Courtship / Humor; Partnerwahl; Kulturwandel; Sozialpsychologie; Technischer Fortschritt